2018
DOI: 10.3390/nu10030379
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of the Adherence to a Mediterranean Diet and Its Main Components with CRP Levels in the Spanish Population

Abstract: Background: Adherence to a Mediterranean diet seems to be inversely associated with C-reactive protein (CRP) concentration. A 14-point Mediterranean Diet Adherence Screener (MEDAS) has been developed to assess dietary compliance. Objective: The aim of this study was to assess whether each of the MEDAS questions as well as their final score were associated with the levels of CRP in general Spanish population. Methods: Cross-sectional analysis of 1411 subjects (mean age 61 years, 43.0% males) randomly selected f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 31 publications
5
34
0
1
Order By: Relevance
“…When analyzing the different components in our study, the effect varies. Thus, a study conducted in the Spanish population [22] found that lower figures for reactive C protein are associated with the consumption of vegetables, fruit, dairy products, and fish, but not with the consumption of olive oil or nuts, two important components of the Mediterranean diet.…”
Section: Discussionmentioning
confidence: 99%
“…When analyzing the different components in our study, the effect varies. Thus, a study conducted in the Spanish population [22] found that lower figures for reactive C protein are associated with the consumption of vegetables, fruit, dairy products, and fish, but not with the consumption of olive oil or nuts, two important components of the Mediterranean diet.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, assessment of dietary patterns is suggested as an important indicator of chronic low-level systemic inflammation, which is an associated factor of chronic diseases [42]. Adherence to a healthy dietary pattern, such as the Mediterranean diet, is inversely associated with blood inflammatory biomarker levels [43,44]. An anti-inflammatory diet with a lower dietary inflammatory index score relates to a higher (i.e., healthier) score on the Healthy Eating Index-2010 [45,46].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the nutrients of a typical ketogenic diet are mainly nonstarchy vegetables, butter, eggs, olive oil, avocados, walnuts, and seeds (Taylor, Swerdlow, Burns, & Sullivan, 2019), many of which, such as olive oil, eggs, vegetables, and walnuts, are characteristic to the Mediterranean diet. Moreover, this diet can further increase the production of KBs without being a typical ketogenic diet; enriching it with foods which contain large amounts of medium-chain triglycerides (MCTs) such as coconut oil (Pehowich, Gomes, & Barnes, 2000), goat's milk (Haenlein, 2004), or butter characteristic of the Mediterranean diet (Dupuis et al, 2004;Lahoz et al, 2018); and proportionally decreasing the percentage of carbohydrates (Paoli, Cenci, & Grimaldi, 2011). Moreover, this diet can further increase the production of KBs without being a typical ketogenic diet; enriching it with foods which contain large amounts of medium-chain triglycerides (MCTs) such as coconut oil (Pehowich, Gomes, & Barnes, 2000), goat's milk (Haenlein, 2004), or butter characteristic of the Mediterranean diet (Dupuis et al, 2004;Lahoz et al, 2018); and proportionally decreasing the percentage of carbohydrates (Paoli, Cenci, & Grimaldi, 2011).…”
Section: Med Iterr Ane An D Ie Tmentioning
confidence: 99%
“…These products, especially fish rich in omega-3 polyunsaturated fatty acids, provide high amounts of KBs (Paoli et al, 2015). Moreover, this diet can further increase the production of KBs without being a typical ketogenic diet; enriching it with foods which contain large amounts of medium-chain triglycerides (MCTs) such as coconut oil (Pehowich, Gomes, & Barnes, 2000), goat's milk (Haenlein, 2004), or butter characteristic of the Mediterranean diet (Dupuis et al, 2004;Lahoz et al, 2018); and proportionally decreasing the percentage of carbohydrates (Paoli, Cenci, & Grimaldi, 2011). In this sense, this combination has been proposed as the "Spanish Ketogenic Mediterranean Diet," in which <30 g of carbohydrates per day is provided and, therefore, it fits under the definition of a ketogenic diet better In addition, as well as being a promising vehicle for KBs, we must highlight the great antioxidant capacity that characterizes this diet.…”
Section: Med Iterr Ane An D Ie Tmentioning
confidence: 99%